CR Image Optimization and Radiation Dose Limitation With Collimation Adjusting on Cervical Radiography - Agustina Dwi Prastanti; Bagus Abimanyu; Andrey Nino Kurniawan; Salis Nurbaiti (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: Radiological examination in cervical services, Radiographers often opening the collimation wider of the size of the imaging plate for fear of being cut. This is done because it is supported by the image cropping facility on the CR. So there is a habit of opening the collimation width as wide as the imaging plate, which is often done with the assumption that it is better to widen the collimation than cut off the object. Obviously this will increase the radiation dose in patients with basic limitations. According to ICRP, patient safety must refer to the principle of radiation protection ALARA namely in the shortest possible time to get quality radiographs and patients receive the most minimum radiation exposure as possible.Methods: This research is a descriptive analytic research conducted with a cross sectional approach. The study was conducted by varying the radiation field area to be used for cervical examination. There are 10 variations of collimation area with 3 (three) exposures in each collimation. Then measured contrast, noise and radiation dose. Radiation dose is calculated by means of a babyline device.Results: The results showed that the collimation setting did not affect contrast radiography in CR because collimation was not the main factor that could affect contrast radiography on CR. The collimation setting on cervical radiography has an effect on the radiation dose, so it is necessary to adjust the collimation to get the minimum dose possible. The most optimal collimation area on cervical radiographic examination was obtained at a size of 12 x 24 cm with the smallest noise reception and dose compared to others and had higher contrast. Average contrast value achieved was 0.45 with a dose of 39.23 µGy.Conclusion: The collimation setting on cervical radiography has an effect on the radiation dose, so it is very necessary to adjust the collimation to get the minimum dose possible. The most optimal collimation area on cervical radiographic examination is obtained at a size of 12 x 24 cm with the smallest noise reception and dose compared to others and has a higher contrast.